2020
DOI: 10.1186/s12950-019-0233-z
|View full text |Cite
|
Sign up to set email alerts
|

Corpus cavernosum smooth muscle cell dysfunction and phenotype transformation are related to erectile dysfunction in prostatitis rats with chronic prostatitis/chronic pelvic pain syndrome

Abstract: Background: The relationship between chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) and erectile dysfunction (ED) has been shown in many studies. However, the specific mechanism remains unclear. This study was to investigate the corpus cavernosum smooth muscle cell function and phenotype transformation in Experimental autoimmune prostatitis (EAP) rats. Methods: EAP was induced in rats by using prostate protein supplemented with immuneadjuvant extraction, and the max-ICP and MAP were measured. IHC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Chronic prostatitis is a disease of young adults under 50 years [8], [40], [41] characterized by voiding symptoms, genitourinary pain, and often sexual dysfunction, that may lead to impaired sexual and reproductive health [7], [8], [42], [43], [44], such as erectile dysfunction and premature ejaculation [42], [45], [46], [47], [48]. Erectile dysfunction is 3.6 times more common in men with chronic prostatitis symptoms [49], and up to 35% of patients with chronic prostatitis experience erectile dysfunction [48]. Premature ejaculation is one of the most common sexual dysfunctions, affecting up to 30% of men, with severe consequences on life quality such, leading to stress, frustration, and even desire to avoid sexual intercourse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic prostatitis is a disease of young adults under 50 years [8], [40], [41] characterized by voiding symptoms, genitourinary pain, and often sexual dysfunction, that may lead to impaired sexual and reproductive health [7], [8], [42], [43], [44], such as erectile dysfunction and premature ejaculation [42], [45], [46], [47], [48]. Erectile dysfunction is 3.6 times more common in men with chronic prostatitis symptoms [49], and up to 35% of patients with chronic prostatitis experience erectile dysfunction [48]. Premature ejaculation is one of the most common sexual dysfunctions, affecting up to 30% of men, with severe consequences on life quality such, leading to stress, frustration, and even desire to avoid sexual intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding to erectile function, an erection occurs when endothelial nitric oxide synthase and neuronal enzymes release, which increases the production of cyclic guanine monophosphate, favoring the relaxation of the arterial wall of the smooth muscle cells of the corpus cavernosum [49]. However, chronic prostatitis altered the relaxation of the arterial wall, and tadalafil has been proposed as a potential treatment [51].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have found that about 29% of CP patients have ED and several clinical cohort studies have confirmed that CP is one of the clinical risk factors of ED (Fan et al., 2020). In recent years, some scholars had found that the phenotype of rat corpus cavernosum smooth muscle cells can transfer from contractile type to synthetic type in EAP rats (Wang et al., 2020). Simultaneously, the penile tissue of EAP rats had endothelial cell damage with a decrease in the expression of eNOS (Huang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The expressions of calponin and α‐SMA were confirmed a decreasing trend in different EAP groups through WB results. Calponin was highly expressed in mature smooth muscle cells and increased with the maturation process (Hossain et al., 2003), but decreased when smooth muscle cells transformed from contractile type to synthetic type (Wang et al., 2020). As a microfilament of the actin family, α‐SMA contained the specificity that can regulate cell morphology and is mainly expressed in differentiated mature vascular smooth muscle cells, of which the expression changes can reflect the smooth muscle cell contractility (Han et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation